Convention on The Rights of Persons With Disabilities: Efforts to Fulfill Human Rights for Access to Workers with Disabilities - Situmorang, Ave Agave Christina; Kusuma, Winanda (Uti Possidetis: Journal of International Law, 2023)
The Convention on The Rights of Persons With Disabilities (CRPD) is a special international human rights instrument that regulates the rights of persons with disabilities as a concrete effort to respect, protect and guarantee the rights of persons with disabilities throughout the world. Indonesia has ratified the convention on the rights of persons with disabilities. Even though Indonesia has ratified the CRPD convention, the fulfillment of human rights (HAM) for Indonesian citizens, especially the rights of persons with disabilities to get a job, has not been maximized. This paper is a research that examines juridically the implementation of the CRPD Convention in Indonesia regarding the employment of persons with disabilities. The research method used by the author is a legal research method focusing on library research. Normative legal research focuses on the study of data such as laws and regulations, legal theory as well as scientific legal research works.